I'm trying to rewrite function "f" in the first line of the picture below in terms of only "x2" and "x3":
Any ideas ? Is it possible ? Thanks in advance.
Solved! Go to Solution.
Would essentially become: f(x2,x3):=2*x2+2*x3
Then if (also): x2=x1+5*x3, it would mean that x2=x2+x3+5*x3, so 0=6*x3 and x3=0 and finally this means that
f is not a function of x3.
Does not make sense.
What exactly do you want?
If both condition have to be considered, as Liuc said, this would mean that x3=0 and x1=x2 and f(x2)=2*x2.
Even with other conditions - if you apply two independend conditions, f would only be dependent on one variable, not on two.
Here are two ways to do it with one condition - not sure if thats waht you are looking for: